2005
DOI: 10.1021/jm058205b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of Pyrazine-Pyridine Biheteroaryls as Novel, Potent, and Selective Vascular Endothelial Growth Factor Receptor-2 Inhibitors

Abstract: There is much evidence that direct inhibition of the kinase activity of vascular endothelial growth factor receptor-2 (VEGFR-2) will result in the reduction of angiogenesis and the suppression of tumor growth. Palladium-catalyzed C-C bond, C-N bond formation reactions were used to assemble various pyrazine-pyridine biheteroaryls as potent VEGFR-2 inhibitors. Among them, 4-{5-[6-(3-chloro-phenylamino)-pyrazin-2-yl]-pyridin-3-ylamino}-butan-1-ol (39) and N-{5-[6-(3-chloro-phenylamino)-pyrazin-2-yl]-pyridin-3-yl}… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The specific role of the bioactivity of pyridine ring has been recognized and the introduction of some pyridine analogs into the molecules of drugs could result in new compounds that have significant biological activity compared with the parent compounds Straub et al, 1997;Bolognese et al, 2002;Tiwari et al, 2002;Kuo et al, 2005). It was also reported that a diverse array of naturally occurring alkaloids in sponges exhibit potent bioactivities because of the presence of a pyridine moiety (Vincent et al, 1997;Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The specific role of the bioactivity of pyridine ring has been recognized and the introduction of some pyridine analogs into the molecules of drugs could result in new compounds that have significant biological activity compared with the parent compounds Straub et al, 1997;Bolognese et al, 2002;Tiwari et al, 2002;Kuo et al, 2005). It was also reported that a diverse array of naturally occurring alkaloids in sponges exhibit potent bioactivities because of the presence of a pyridine moiety (Vincent et al, 1997;Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other halogen-containing compounds are the inhibitors of VEGFR-2 ZD4190, ZD6474, PTK787 and KRN951, and the bromotyrosine aeroplysinin-1 isolated from several marine sponges (3,23). Structure-function studies with quinazolinamino-benzoquinones and pyrazine-pyridine biheteroaryls reveal that halogen substitution increases the activity of the compounds as inhibitors of the kinase domain of VEGFR-2 (24,25). Although evidences point out to the relevance of electron-withdrawing halogen substituents in the antiangiogenic inhibitor molecules, their role in the mechanism of the reaction involved in the inhibition of the receptor tyrosine kinase activity remains obscure and deserves further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The studied dataset was taken from the published work [17]. The 32 compounds investigated are listed in Table 1.…”
Section: Datasetsmentioning
confidence: 99%
“…Generally, RNB reflects the p electron density of the molecule and hence influences the interaction between the drug and its receptor. Though NH of the side chain, directly attached to the biheteroaryl, is a hydrogenbond donor site [17]. Considering the structures as a whole, N atom mostly serves as a hydrogen-bond acceptor and more hydrogen-bond donors must come from the receptor.…”
Section: Explanation Of Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation